Introduction to the Focus Issue. Issue 4 (30th July 2013) - Hamaker, Bruce; Seetharaman, Koushik; Bertoft, Eric
Abstract : Cereal biomacromolecules are an important source not just of calories but also of functional ingredients in foods and as raw materials for biodegradable nonfood applications. Their important role is evidenced by an ever‐increasing number of peer‐reviewed publications on these topics. Current research is increasingly focused on understanding the fine structure of the macromolecules and their interactions with other ingredients within a food matrix for their impact on health. Furthermore, these learnings about the fine structure and interactions have relevance to functionality in nonfood applications. This focus issue attempts to summarize the state of the knowledge and research gaps related to the three major biomacromolecules in cereals: starch, proteins, and nonstarch polysaccharides (dietary fiber). Click onCurrent Issues on left and thenJuly/August 2013 to view the articles in this Focus Issue. (From the Mobile site, go to the July/August 2013 issue.)